2017
DOI: 10.1113/ep086463
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin mediates the beneficial effects of the exercise training on breast cancer

Abstract: What is the central question of this study? We hypothesized that potential anti-tumour effects of exercise training might be mediated by oxytocin and explored the underlying mechanisms in a mouse model of breast cancer. What is the main finding and its importance? Interval exercise training, by inducing oxytocin secretion, may reduce the activity of the PI3K/Akt and ERK pathways, and consequently, results in a smaller tumour volume in a mouse model of breast cancer. Exercise training can affect the growth of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…A mouse xenograft model study demonstrated that OT can mediate the beneficial effects of physical exercise on breast cancer growth. Both exercise and OT administration decreased tumour volume and weight, and OT plasma concentration in the tumour and exercise group was more than 10-fold higher than in the tumour control group (tumour without exercise) [56]. OT levels in the pituitary and blood also increased in a rat breast cancer model induced by N-methyl-nitrosourea (NMU)-treatment due to inhibition of insulin-regulated aminopeptidase (an oxytocinase) and decrease of catabolism of OT in the hypothalamus [57].…”
Section: Protective Effects Of Ot Against Breast Cancer Developmentmentioning
confidence: 81%
See 2 more Smart Citations
“…A mouse xenograft model study demonstrated that OT can mediate the beneficial effects of physical exercise on breast cancer growth. Both exercise and OT administration decreased tumour volume and weight, and OT plasma concentration in the tumour and exercise group was more than 10-fold higher than in the tumour control group (tumour without exercise) [56]. OT levels in the pituitary and blood also increased in a rat breast cancer model induced by N-methyl-nitrosourea (NMU)-treatment due to inhibition of insulin-regulated aminopeptidase (an oxytocinase) and decrease of catabolism of OT in the hypothalamus [57].…”
Section: Protective Effects Of Ot Against Breast Cancer Developmentmentioning
confidence: 81%
“…Meanwhile, inhibition of PLC with its inhibitor U73122 also abolished the inhibition of cell growth by OTR coupling to Gα i , which is possibly a result of PLC activation by the βγ complexes released by Gα i [115]. The Gα i pathway appears to also mediate breast cancer growth inhibitory effects of OT, with the involvement of the PI3K/Akt pathway [56,97]. In MCF-7 cells, which express OTR and feature a PI3K activating mutation, a 30 min incubation with OT (125-1,000 nM) reduced the abundance of PI3K signalling components, including a reduction of PI3K p85, PI3K p110, and pAktS 473 , and Akt phosphorylation downstream of OTR requires Gα i and a structural change in the receptor [116].…”
Section: G Protein-dependent Signalling Of Otrmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, anti-proliferative and tumor inhibitory properties were also observed in vivo in both rat and mouse experimental models, and attributed to both oxytocin and its analogue F314[ 9 ]. Recently, it was suggested that exercise training, by inducing oxytocin secretion, may reduce the expression of specific signaling proteins involved in breast cancer[ 59 ].…”
Section: Oxytocin In Cancermentioning
confidence: 99%
“…The positive impact of exercise in blunting development of cancer and facilitating recovery may potentially be partly mediated through oxytocin. For example, oxytocin has been proposed to mediate an exercise-induced reduction in the expression of specific signaling molecules involved in breast cancer[ 59 ]. It has also recently been shown in vivo that the combination of exogenous oxytocin with exercise improves cardiac function, which might be associated with improved cancer survival.…”
Section: Oxytocin In Cancermentioning
confidence: 99%